Pengaruh Politik Hukum Amerika Serikat Terhadap Konflik Global Dan Dampaknya Pada Politik Hukum Indonesia - Prabowo, Andrianto; Irma Mangar; Nico Ferdian (Universitas Pancasakti Tegal, 2026)
This research aims to analyze the influence of the political law of the United States on the dynamics of global conflicts and its impact on the development of legal politics in Indonesia. The method used is a qualitative approach with descriptive analysis of various international legal and political phenomena. The results of the study show that the legal politics of the United States have an expansive and strategic character, where the law is used as an instrument to legitimize global geopolitical interests. Policies such as the